Thermodynamic stability and energetics of DNA duplexes containing major intrastrand cross-links of second-generation antitumor dinuclear Pt(II) complexes - Florián, Jakub; Kašpárková, Jana; Farrell, Nicholas P; Brabec, Viktor (JBIC, Journal of biological inorganic chemistry, 2012)
The effects of major DNA intrastrand cross-links of antitumor dinuclear Pt(II) complexes [{trans-PtCl(NH(3))(2)}(2)-μ-{trans-(H(2)N(CH(2))(6)NH(2)(CH(2))(2)NH(2)(CH(2))(6)NH(2))}](4+) (1) and [{PtCl(DACH)}(2)-μ-{H(2)N(CH(2))(6)NH(2)(CH(2))(2)NH(2)(CH(2))(6)NH(2))}](4+) (2) (DACH is 1,2-diaminocyclohexane) on DNA stability were studied with emphasis on thermodynamic origins of that stability. Oligodeoxyribonucleotide duplexes containing the single 1,2, 1,3, or 1,5 intrastrand cross-links at guanine residues in the central TGGT, TGTGT, or TGTTTGT sequences, respectively, were prepared and analyzed by differential scanning calorimetry. The unfolding of the platinated duplexes was accompanied by unfavorable free energy terms. The efficiency of the cross-links to thermodynamically destabilize the duplex depended on the number of base pairs separating the platinated bases. The trend was 1,5→1,2→1,3 cross-link of 1 and 1,5→1,3→1,2 cross-link of 2. Interestingly, the results showed that the capability of the cross-links to reduce the thermodynamic stability of DNA (ΔG(298)(0)) correlated with the extent of conformational distortions induced in DNA by various types of intrastrand cross-links of 1 or 2 determined by chemical probes of DNA conformation. We also examined the efficiency of the mammalian nucleotide excision repair systems to remove from DNA the intrastrand cross-links of 1 or 2. The efficiency of the excinucleases to remove the cross-links from DNA depended on the length of the cross-link; the trend was identical to that observed for the efficiency of the intrastrand cross-links to thermodynamically destabilize the duplex. Thus, the results are consistent with the thesis that an important factor that determines the susceptibility of the intrastrand cross-links of dinuclear platinum complexes 1 and 2 to be removed from DNA by nucleotide excision repair is the efficiency of these lesions to thermodynamically destabilize DNA.
Keywords: konformace nukleové kyseliny; Calorimetry, Differential Scanning; Nucleic Acid Conformation; protinádorové látky; sekvence nukleotidů; Intercalating Agents; oprava DNA; interkalátory; termodynamika; DNA Repair; Organoplatinum Compounds; Thermodynamics; organoplatinové sloučeniny; Antineoplastic Agents; Base Sequence; DNA; diferenciální skenovací kalorimetrie